2017
DOI: 10.1016/j.fertnstert.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on sperm banking attempts among adolescent males newly diagnosed with cancer

Abstract: NCT01152268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Post‐hoc analyses of our data also support this finding, as patients whose parents were available and willing to participate in our study were more likely to bank sperm than patients whose parents did not complete a survey, Χ 2 (1) = 3.8, P < 0.05. This study demonstrates that over half of parents (59%) support sperm banking, which is important when other research reports up to 80% of AYAs engage in a shared banking decision‐making process with their parents 20 and our previously published results demonstrate that 80% of these AYA males who receive a parent recommendation make a collection attempt (57/71) and over 75% of those without a recommendation fail to make an attempt (36/46) 17 . As such, efforts to investigate factors that encourage or discourage parent recommendation to sperm bank are warranted and should remain a target for intervention when working with families in pediatric and/or young adult oncology.…”
Section: Discussionsupporting
confidence: 59%
“…Post‐hoc analyses of our data also support this finding, as patients whose parents were available and willing to participate in our study were more likely to bank sperm than patients whose parents did not complete a survey, Χ 2 (1) = 3.8, P < 0.05. This study demonstrates that over half of parents (59%) support sperm banking, which is important when other research reports up to 80% of AYAs engage in a shared banking decision‐making process with their parents 20 and our previously published results demonstrate that 80% of these AYA males who receive a parent recommendation make a collection attempt (57/71) and over 75% of those without a recommendation fail to make an attempt (36/46) 17 . As such, efforts to investigate factors that encourage or discourage parent recommendation to sperm bank are warranted and should remain a target for intervention when working with families in pediatric and/or young adult oncology.…”
Section: Discussionsupporting
confidence: 59%
“…Reasons for exclusion are depicted in Figure . A total of 42 studies could be included in this review (Achille et al, ; Armuand et al, ; Babb et al, ; Bann et al, ; Boltezar et al, ; Branvall et al, ; Brydøy et al, ; Chang, Chen, Chen, & Hsieh, ; Crha et al, ; Fitoussi et al, ; Gilfillan et al, ; Girasole et al, ; Greaves et al, ; Grover, Deal, Wood, & Mersereau, ; Harrison, Welch, Matook, & Schwartz, ; Hoshi et al, ; van der Kaaij et al, ; Kamimura, Matsumoto, Zhou, Moriyama, & Saijo, ; Kelvin et al, ; Klosky, Anderson, et al, ; Klosky, Flynn, et al, ; Klosky et al, ; Klosky, Wang, et al, ; Kumar, Merali, Pond, & Zbuk, ; Latif & Ali, ; Naccache et al, ; Neal et al, ; Noetzli et al, ; Pacey et al, ; Ping, Gu, Li, Huang, & Li, ; Ramstein et al, ; Richter, Mehnert, & Geue, ; Rieker, Fitzgerald, & Kalish, ; Rooney et al, ; Rotker et al, ; Schover et al, ; Schover, Rybicki, Martin, & Bringelsen, ; Sheth et al, ; Shnorhavorian et al, ; Sonnenburg, Brames, Case‐Eads, & Einhorn, ; Wang, Chen, Ruan, & Cheung, ; Xu et al, ). No additional study could be identified by checking the references of included papers, and we did not receive any additional relevant studies by contacting the corresponding authors of included trials.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies followed a retrospective approach (38/42). Only four trials were executed prospectively: Hoshi et al () (Japan): 11 patients; Klosky, Flynn, et al () (USA and Canada): 146 patients; Klosky, Wang, et al () (USA and Canada): 99 patients; and Klosky, Flynn, et al () (USA and Canada): 122 patients. Three studies comprise more than one cohort (Kelvin et al, ; Klosky, Wang, et al, ; Rotker et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertility and sexual/reproductive health are sensitive topics, often difficult to discuss within families . A recent study conducted immediately after the initiation of cancer treatment highlighted the importance of parent involvement in sperm banking decisions . However, AYAs and their parents may have discordant reproductive goals/concerns at the time of a new cancer diagnosis and in survivorship .…”
mentioning
confidence: 99%